Warpage minimisation on side arm using response surface methodology (RSM) - Shazzuan Shahari (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
The aim of this research is to minimise the warpage issue in the Nylon PA66 side arm products produced by injection moulding process. This aim can be achieved by the following specific objectives ; to investigate the most significant factor influencing the warpage on the side arm parts ; to evaluate the best setting of processing parameters to minimise warpage on the side arm parts ; to compare the warpage value on the side arm parts after optimisation against the recommended settings from simulation studies.